Design of New V Shaped Thermotropic Liquid Crystals containing Heterocyclic - Athraa J. Ali, Nisreen H. Karam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The characterization and design of this study of new liquid crystals with a V shape compounds containing thiazolidine-2,4-dione and 1,3-phenylene as a core unite with mesophase properties were reported. Preparation and characterization of chloroacetic acid, water, and thiourea to produce thiazolidine-2,4-dione [I] in the presence of strong hydrochloric acid. The 4-hydreoxybenzaldehyde and n-alkyl bromide were reacted with potassium hydroxide to create the n-alkoxy benzaldehyde., then the compound [I] reacted with [II]n in presence of piperidine to produce compounds [III]n. Also, converted resorcinol to a corresponding compound [IV] by refluxing pyridine and DMF with two moles of chloracetyl chloride, after that interacted the compounds [III]n and compound [IV] with sodium acetate to form compounds [V]n. FT-IR and 1HNMR spectroscopy were really used to determine the structures of the produced substances. Using polarized optical microscopy, these mesogens’ mesomorphic characteristics were studied (POM).The synthesized molecules exhibited enantiotropic liquid crystal phases, the substances [V]1-4 exhibited an only the enantiotropic nematic phase.